The Impact of Inflation and GDP Growth Rate on Nepal’s Stock Market: An Analytical Study - Adhikari, C. P.; Jha, A. K.; Maheshwari, D. N. (Medha: A Multidisciplinary Journal, 2024)
This study explores the impact of macroeconomic variables, particularly the inflation rate and GDP growth rate, and their influence on Nepal’s stock market, as measured by the NEPSE Index by using regression analysis. The NEPSE Index as a measure of economic performance, reflects market dynamics and investor sentiment, which are influenced by inflation and GDP growth rates. The regression model explains 50.78% of the variation in the NEPSE index, as indicated by the R Square value. The analysis reveals a significant negative relationship between GDP growth rate and the NEPSE index, with a coefficient of -154.43 and a p-value of 0.0258. Conversely, the inflation rate exhibits a negative but statistically insignificant impact, with a coefficient of -149.83 and a p-value of 0.0630. These findings suggest that while the GDP growth rate significantly affects stock market performance, inflation’s influence may be less pronounced or mediated by other factors. The results also highlight the presence of unexplained variance, indicating the role of additional factors not captured in the model. Based on the findings, the study recommends incorporating more macroeconomic variables, increasing sample size, and conducting sectoral analyses to enhance the robustness of future research. Policymakers and investors are advised to consider broader economic and structural factors when making decisions to foster a resilient and efficient stock market in Nepal. Overall, this analysis provides essential knowledge for decision-making in investment strategies and economic policy making.